2023
DOI: 10.1021/acsaem.3c01243
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Utilization Boundaries for Pt-Based Catalysts in an Operating Proton-Exchange Membrane Fuel Cell

Michal Ronovsky,
Lujin Pan,
Malte Klingenhof
et al.

Abstract: Octahedra (oh) PtNiX/C catalysts are notable cathode catalysts for proton-exchange membrane fuel cells due to their exceptional oxygen reduction reaction activity. Here, we investigate the degradation of oh-PtNiIr catalysts under fuel-cell conditions using operando X-ray diffraction (XRD). Employing two accelerated stress tests with different lower potential limits and XRD-coupled cyclic voltammetry on benchmark Pt and oh-PtNiIr catalysts, we find that dissolution and degradation are proportional to the extent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 30 publications
2
6
0
Order By: Relevance
“…In accordance with the assumptions from the results obtained using the HT-DE methodology ( Figure 3 ), the signals for both Pt and Co dissolution decrease substantially with the narrowing potential window from 0.6–0.95 V RHE ( Figure 4 a, c,e) to 0.7–0.85 V RHE ( Figure 4 b,d,f) regardless of the applied hold time at each potential. This has also been reported by previous studies, 43 , 45 , 48 , 66 , 68 , 69 but what is specific here is that both LPL and UPL are nevertheless limited to a realistic operational voltage while positively affecting the stability of both metals. What is also important to emphasize here is that dissolution during cycling when limiting both potential limits (LPL as well as UPL) is, however, not completely suppressed but only significantly reduced, i.e., minimized.…”
Section: Resultssupporting
confidence: 88%
See 4 more Smart Citations
“…In accordance with the assumptions from the results obtained using the HT-DE methodology ( Figure 3 ), the signals for both Pt and Co dissolution decrease substantially with the narrowing potential window from 0.6–0.95 V RHE ( Figure 4 a, c,e) to 0.7–0.85 V RHE ( Figure 4 b,d,f) regardless of the applied hold time at each potential. This has also been reported by previous studies, 43 , 45 , 48 , 66 , 68 , 69 but what is specific here is that both LPL and UPL are nevertheless limited to a realistic operational voltage while positively affecting the stability of both metals. What is also important to emphasize here is that dissolution during cycling when limiting both potential limits (LPL as well as UPL) is, however, not completely suppressed but only significantly reduced, i.e., minimized.…”
Section: Resultssupporting
confidence: 88%
“…Namely, varying the LPL in the range of 0.7/0.65/0.6 V RHE , with a constant UPL (0.925 V RHE ), provided evidence that the cathodic dissolution of both Pt as well as less noble metal increases with a decrease in LPL. In line with this study, Ronovsky et al 45 provided a comprehensive XRD study on the stability of an octahedral-PtNiIr electrocatalyst during MEA square-wave accelerated degradation tests (ADTs) with a constant UPL (0.95 V) and LPL varying from 0.6 to 0.7 V. Dissolution of Pt and Ni has been tracked by observing three XRD parameters (scattering intensity, lattice parameter, and crystallite size), and a strong dependence of the stability of Pt-alloy based electrocatalyst on the LPL has been confirmed once again. The authors have observed that the extent of degradation of the analyzed electrocatalyst is proportional not only to the degree of Pt oxidation but also to the degree of reduction of the formed Pt oxide.…”
Section: Introductionsupporting
confidence: 89%
See 3 more Smart Citations